In the translation T of the graph below, use the figure to describe the Following transformation.
![In the translation T of the graph below use the figure to describe the Following transformation class=](https://us-static.z-dn.net/files/d5a/f00570bdb1899acffe30207516e6ca16.png)
Answer:
(a) (x -6, y -2)
Step-by-step explanation:
You seem to want to see the inverse of the translation T, applied twice. Your notation seems to mean ...
For T = (x, y) +(a, b)
T⁻¹ = (x, y) -(a, b) ⇒ T⁻² = (x, y) -2(a, b)
__
Your given transformation is ...
T = (x, y) +(3, 1)
which means ...
T⁻² = (x, y) -2(a, b) = (x, y) -2(3, 1)
T ⁻² = (x -6, y -2)